Disaster Risk Management and Fiscal Policy : Narratives, Tools, and Evidence Associated with Assessing Fiscal Risk and Building Resilience - Mechler, Reinhard (World Bank, Washington, DC, 2016)
This paper addresses the question whether and how co-benefits, through disaster resilience building, can be further promoted. Co-benefits are defined as positive externalities that arise deliberately as a result of a joint strategy that pursues several objectives synergistically at the same time, such as disaster risk management and development goals, or disaster risk management and climate change adaptation. Of particular interest is the question of how the economic and broader benefits of disaster risk management can be recognized and realized by those in charge of fiscal policy decisions. The paper considers the interplay between public disaster risk management investment and fiscal policy, and provides an overview of the current debate as well as assessment methods, tools, and policy options. In fiscal budgeting, it has been standard practice to focus on direct liabilities and recurrent spending. Costs of disasters are often dealt with after the fact only, rather than being considered as contingent liabilities. As a consequence, the full costs of disasters have often not been budgeted for, and, with a price signal missing, there is lack of clear incentives for investing in disaster risk management. Overall, the paper identifies four steps and three dividends to be harnessed: (i) understanding fiscal risk; (ii) protecting public finance through risk financing instruments, the first dividend; (iii) managing disaster risk comprehensively, the second dividend; and (iv) pursuing a synergistic, co-benefits strategy of concurrently managing disaster risks and promoting development, the third dividend.